African Modernity and the Philosophy of Culture in the Works of Femi Euba. - Osagie, Iyunolu; Lowe, John Wharton (Blue Ridge Summit : Lexington Books/Fortress Academic, 2017)
This book examines the creative and critical works of Nigerian playwright and novelist Femi Euba to demonstrate the place and function of African cultures in modernity. The author makes the case for the vibrancy of such cultures in the shaping and constitution of the modern world.
Intro -- Contents -- Acknowledgments -- Foreword -- Preface -- Chapter One: Archetypes of Modernity -- Chapter Two: Tradition, Modernity, and the Axiological Present in The Gulf and The Eye of Gabriel -- Chapter Three: Black Theatre and the Politics of Adaptation in Dionysus of the Holocaust -- Chapter Four: Who Pulled the Trigger? Ritual Endings in Femi Euba's A Riddle of the Palms, Crocodiles, and The Chameleon -- Chapter Five: Esu as Shape Shifting Word -- Afterword -- Bibliography -- Index -- About the Author.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Euba, Femi--Criticism and interpretation; Electronic books